Comparison of Male and Female Resident Milestone Assessments During Emergency Medicine Residency Training: A National Study. (February 2020) - Santen, Sally A.; Yamazaki, Kenji; Holmboe, Eric S.; Yarris, Lalena M.; Hamstra, Stanley J.
Abstract : Purpose: A previous study found that milestone ratings at the end of training were higher for male than for female residents in emergency medicine (EM). However, that study was restricted to a sample of 8 EM residency programs and used individual faculty ratings from milestone reporting forms that were designed for use by the program's Clinical Competency Committee (CCC). The objective of this study was to investigate whether similar results would be found when examining the entire national cohort of EM milestone ratings reported by programs after CCC consensus review. Method: This study examined longitudinal milestone ratings for all EM residents (n = 1, 363; 125 programs) reported to the Accreditation Council for Graduate Medical Education every 6 months from 2014 to 2017. A multilevel linear regression model was used to estimate differences in slope for all subcompetencies, and predicted marginal means between genders were compared at time of graduation. Results: There were small but statistically significant differences between males' and females' increase in ratings from initial rating to graduation on 6 of the 22 subcompetencies. Marginal mean comparisons at time of graduation demonstrated gender effects for 4 patient care subcompetencies. For these subcompetencies, males were rated as performing better than females; differences ranged from 0.048 to 0.074 milestone ratings. Conclusions: In this national dataset of EM resident milestone assessments by CCCs, males and females were rated similarly at the end of their training for the majority of subcompetencies. Statistically significant but small absolute differences were noted in 4 patient care subcompetencies.